A Case of West Nile Encephalitis That Develops into a Disease of Deep White Matter on MRI over a Two-Week Span - Adam Puchalski; Antonio Liu (Case Reports in Neurological Medicine)
We present a case of serologically proved West Nile encephalitis. This patient had a normal MRI on admission. Given that the patient’s clinical picture had worsened during her admission, a repeat MRI was performed, which demonstrated diffuse disease in the deep white matter of the brain. This is a case of West Nice encephalitis presenting as a disease of deep white matter that developed over a two-week span.